Food Waste Treatment by High-Temperature and High-Pressure Steam - Hee Han, Doo; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: There were many limitations in the processing of food wastes, such as immaturity and salt excess. After processing, recycling to compost or feed requires faster processing times and reduced odor and leachate. A recycling apparatus of organic wastes by using direct steam heating is proposed in this paper for composts and animal food. Methods/Statistical analysis: There are many processes to treat food waste, but in order to reduce the odor, a method of circulating the steam in a closed space and cooling and discharging is used. In this case, the solid material is effectively dried and the liquid component is discharged to about 20,000 ppm. In the case of animal food, saturated steam of 3.2 atm. and 135â„ƒ was used in order to decompose to water. Also, saturated steam of 16 atm. and 200â„ƒ was used in order to hydrolyze, to acidhydrolyze, to prolyze, to carbonize the food waste. Condensed water can be used to liquid compost, the organic waste can be totally recycled. Findings When food waste is dried with high-temperature high-pressure steam at 200Â°C and 16 atmospheres, the 1 ton scale can be treated in one hour. However, careful attention should be paid to the high-pressure machine management. Improvements/Applications: Effective ways to reduce salinity should be considered when using small-scale machines to effectively dry garbage. Salinity-rich composts can damage crops Â Â